Investigating the Passivity and Dissolution of a Corrosion Resistant Mg-33at.%Li Alloy in Aqueous Chloride Using Online ICP-MS. Issue 6 (1st January 2016) - Hou, Lifeng; Raveggi, Massimo; Chen, Xiao-Bo; Xu, Wanqiang; Laws, Kevin J.; Wei, Yinghui; Ferry, Michael; Birbilis, Nick
Abstract : The corrosion and dissolution of a new magnesium-lithium (Mg-Li) alloy was studied using an electrochemical flow cell coupled with inductively coupled plasma - mass spectroscopy (ICP-MS) allowing real-time spectroelectrochemical analysis. The alloy studied is a corrosion resistant Mg-33at. % Li alloy, which possesses a body centered cubic matrix and a homogenous nanostructure. A detailed investigation of the dissolution kinetics of this alloy is important for understanding the origins of its apparently high corrosion resistance. Whilst the alloy composition ratio of Mg:Li is ∼2, it was revealed that the dissolution ratio of metallic Mg:Li in 0.01 M NaCl was ∼3.4 via downstream detection of ions. The deficiency of Li detected in the downstream electrolyte via ICP-MS was attributed to the development of a persistent Li-rich surface film that forms dynamically in the open circuit condition and for applied potentials below ∼−1050 mVAg/AgCl . For potentials positive to ∼−1050 mVAg/AgCl, significant Li ion detection in solution was observed, commensurate with the alloy compositional ratio.